Industrial sickness and workers: case of Gujarat textile industry - Mehta, S.S.; Harode, Dinesh (1998)
Closure of industrial units in developing economies may lead to serious consequences since their limited investible resources and relatively limited alternative employment opportunities cannot easily absorb resultant loss of jobs, production and revenue. Moreover, the present legal and institutional framework to deal with the problem of industrial sickness in India has been found inadequate, particularly in protecting the interests of the workers. The textile crisis in Gujarat makes the inadequacies of present framework quite glaring. - Reproduced
Keywords: Labour - India - Gujarat; Textile industry - India - Gujarat; Textile industry